THE ROLE OF THE POM AGENCY IN CONTROLLING ANTIMICROBIAL RESISTANCE AS IMPLEMENTATION OF HEALTH LAW NUMBER 36 OF 2009 - Yulia Rahmawati (Indonesia Private Law Review, 2023)
The incidence of antimicrobial resistance (AMR) worldwide is getting worse. The issue of antimicrobial resistance, or AMR, is a new health threat and constitutes 1 in 10 world health threats. AMR is a serious problem in the world of health that must be addressed. Therefore, further studies will be carried out on AMR control by the government according to Health Law Number 36 of 2009 and examine the role of the POM in controlling AMR. This paper uses a normative research method, namely finding material from the literature or applicable regulations and conducting a qualitative analysis. The results of this study, the government has tried to fulfill the mandate of the Health Law by creating integrated AMR control across sectors through Permenko No 7/2021 concerning the National Action Plan for Antimicrobial Control. In addition, the Food and Drug Supervisory Agency laid out the AMR control policy through the Decree of the Head of BPOM No. HK.02.02.1.2.03.20.98 of 2020